2007
DOI: 10.1002/ejoc.200700599
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Carbonylation of 2‐Haloselenophenes: Synthesis of Selenophene‐2‐carboxamides, Selenophene‐2,5‐dicarboxamides and N,N′‐Bridged Selenophene‐2‐carboxamides

Abstract: We present herein our results on the palladium-catalyzed carbonylation of 2-haloselenophene and amines, under carbon monoxide atmosphere, giving a new route to prepare selenophene-2-carboxamides, selenophene-2,5-dicarboxamides and N,NЈ-bridged selenophene-2-carboxamides in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The carbonylation of haloselenophenes with amines catalyzed by 10 mol-% palladium in the presence of sodium carbonate was reported by Zeni et al to afford selenophenes-2-carboxamides in good yields (Scheme 15). [41] Selenophene-2,5-dicarboxamides and N,NЈ-bridged selenophene-2-carboxamides could also be obtained by stoichiometric control of 2-haloselenophene and a diamine.…”
Section: Metal-mediated Syntheses Of Organoselenium Compounds Palladi...mentioning
confidence: 99%
“…The carbonylation of haloselenophenes with amines catalyzed by 10 mol-% palladium in the presence of sodium carbonate was reported by Zeni et al to afford selenophenes-2-carboxamides in good yields (Scheme 15). [41] Selenophene-2,5-dicarboxamides and N,NЈ-bridged selenophene-2-carboxamides could also be obtained by stoichiometric control of 2-haloselenophene and a diamine.…”
Section: Metal-mediated Syntheses Of Organoselenium Compounds Palladi...mentioning
confidence: 99%
“…Only a few studies relating to this subject have been reported to date; they include the synthesis of dicarboxamides through aminocarbonylation of diiodo substrates, [28] or through the application of diamines as N-nucleophiles. Among the latter, the synthesis of selenophene derivatives [29] and our recent work on the preparation of 5α-androst-16-ene dimers [30] are the only examples reported so far.…”
Section: Introductionmentioning
confidence: 97%
“…In the field of materials science, they have interesting characteristics, such as organic light-emitting diodes (OLEDs) [ 20 , 21 , 22 , 23 ], organic field-effect transistors (OFETs) [ 24 , 25 , 26 ], organic solar cells (OSC) [ 27 , 28 , 29 , 30 , 31 ], and thin-film transistors [ 32 , 33 , 34 ]. In addition, selenophenes pre-activated with a halide or an organometallic (Li, Mg, Sn or Zn) can be used as building blocks in the formation of new C-C [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ], C-N [ 42 , 43 , 44 ] and C-S [ 45 ] bonds under metal-catalyzed conditions. Alternatively, inactivated selenophenes have been used as reagents in several synthetic transformations, through palladium-catalyzed direct C-H bond activation [ 46 , 47 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%